2008
DOI: 10.1021/la800378c
|View full text |Cite
|
Sign up to set email alerts
|

Role of Superheated Water in the Dissolution and Perturbation of Hydrogen Bonding in the Crystalline Lattice of Polyamide 4,6

Abstract: Here, we demonstrate that water, in the superheated state, is a solvent for polyamide 4,6 (PA4,6) and that the water molecules can strongly influence hydrogen bonding. In the presence of superheated water, the melting temperature of PA4,6 can be suppressed by nearly 100 degrees C. The depression in the melting temperature follows the Flory-Huggins principle. The instantaneous dissolution of the polymer hardly influences the molar mass of the polymer. However, if the polymer is retained in solution above the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
129
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(140 citation statements)
references
References 33 publications
9
129
2
Order By: Relevance
“…In the latter phase, H-bonds make it possible for water to solvate the polyamide blocks [18]. HPDSC measurements were also performed at different pressures (20,40,60 and 80 bar, not reported here). Whatever the pressure, the melting point of the PEBA/water phase appears at the same temperature (153.5°C).…”
Section: Analysis Of Peba-water Solubilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter phase, H-bonds make it possible for water to solvate the polyamide blocks [18]. HPDSC measurements were also performed at different pressures (20,40,60 and 80 bar, not reported here). Whatever the pressure, the melting point of the PEBA/water phase appears at the same temperature (153.5°C).…”
Section: Analysis Of Peba-water Solubilitymentioning
confidence: 99%
“…Furthermore, due to their highly polar amide functions, polyamides are hydrophilic materials. PAwater solubility under temperature and pressure conditions has widely been reported in the literature [18][19][20][21][22][23][24]. Considering this peculiar behavior of polyamides and that montmorillonite platelets are separated from each other in water (constituting a colloidal dispersion), attempts have been made to elaborate PA/pristine clay nanocomposites by melt extrusion with the aid of water.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the crystallization temperature of PA 6 from aqueous solution decreases compared with that from the melt. The dissolution process of PA 6 in superheated water is a process in which water molecules break the hydrogen bonding between amide groups in PA 6 and then make PA 6 dissolve in superheated water [11,12] . It was reported that the Brill transition temperature (T B ) of PA 6 was 160 C [24,25] , which should be helpful for the PA 6 dissolution in water.…”
Section: Resultsmentioning
confidence: 99%
“…Rastogi et al demonstrated that Nylon 46 can dissolve rapidly in superheated water at ~200 C, and re-crystallize on cooling [11,12] . A hydrolysis process is hard to avoid when polyamides dissolved in superheated …”
Section: Introductionmentioning
confidence: 97%
“…As discussed earlier, urea has four hydrogen bonding per unit of molecule, even if all the four hydrogen cannot engage in hydrogen-bonding, still has high capability of hydrogen-bonding interactions. On the other hand, PA chains contain amide groups which are the strong hydrogen bonding donor/acceptor groups [19], while FA has only one hydrogen bonding per unit of molecule. Therefore, the mixture of FA/urea will have a higher tendency to penetrate into the PA chains.…”
Section: Resultsmentioning
confidence: 99%